Analisis Peran Sistem Pembayaran Pajak Digital Dan Literasi Digital Terhadap Kepatuhan Wajib Pajak Orang Pribadi : Analysis of the Role of Digital Tax Payment Systems and Digital Literacy on Individual Taxpayer Compliance - Aliy Rasyid; Abdillah; Devi Setiawan (Jurnal Bisnis dan Ekonomi, 2025)
Abstract:Objective: The purpose of this study is to analyze how individual taxpayer compliance (WPOP) in West Java Province is influenced by e-filing, e-billing, and digital literacy. The phenomenon of tax digitalization serves as the background to this research. Although this trend is projected to increase the ease, effectiveness, and accuracy of tax reporting and payment, the current level of taxpayer compliance remains below ideal standards.Methodology: This is a quantitative study using a survey method. Primary data was obtained by distributing questionnaires to 80 individual taxpayer respondents in West Java Province. The sampling technique used purposive sampling. Data analysis was performed using multiple linear regression using SPSS version 25 software.Research Results: The results indicate that, partially, e-filing has no significant effect on WPOP compliance, e-billing also has no significant effect on WPOP compliance, while digital literacy has a positive and significant effect on WPOP compliance. Simultaneously, e-filing, e-billing, and digital literacy significantly influenced taxpayer compliance with a coefficient of determination (R²) of 0.086. This means that the independent variables in this study explained 8.6% of the variation in taxpayer compliance, while the remaining 91.4% was influenced by factors outside the research model. Based on these findings, the Directorate General of Taxes is recommended to increase taxpayer socialization, education, and digital literacy to optimize the use of the digital tax system in encouraging tax compliance.Keywords: e-filing, e-billing, Digital Literacy, Individual Taxpayer Compliance.